Bending collapse analysis for thin and medium-thin-walled square and rectangular hollow shapes - Lavayen-Farfan D. (2021)
D. Lavayen would like to recognize the financial support provided by CONCYTEC (Peru) and The World Bank, through the Pontifical Catholic University of Peru and FONDECYT (Peru): ?Funding Contract N?10-2018-FONDECYT/WB PhD programs in strategic and general areas?. Part of this work has also been supported by Comunidad de Madrid - multiannual agreement with UC3M (?Excelencia para el Profesorado Universitario? - EPUC3M21) - Fifth regional research plan 2016-2020, The authors would also like to thank Dr. M. A. Martinez-Casanova from the Materials Science and Engineering and Chemical Engineering Department at UC3M for his help during testing. All authors approved the version of the manuscript to be published.